2020
DOI: 10.1093/jjco/hyaa126
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary and repeated recurrent retroperitoneal liposarcoma: outcomes after aggressive surgeries at a single institution

Abstract: Objective This study sought to investigate the characteristics of primary and repeated recurrent retroperitoneal liposarcoma. Methods Patients treated with primary or recurrent retroperitoneal liposarcoma between 2005 and 2018 were retrospectively reviewed. Survival time analysis of recurrence-free survival and overall survival was conducted using Kaplan–Meier analysis and log-rank test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…The PRISMA flow diagram showing the entire review process from the original search to the final selection of studies is presented in Fig 1 . In total, 17 studies (3875 participants) compared between extended resection and tumour resection alone [ 10 , 19 , 20 , 22 , 23 , 31 , 32 , 38 , 44 , 45 , 48 , 51 , 53 , 56 , 57 , 59 , 60 ]. Meanwhile, 26 studies (17368 patients) reported data on different surgical resection margins [ 12 , 17 , 18 , 20 , 21 , 24 28 , 33 – 36 , 40 43 , 46 , 47 , 49 , 50 , 52 , 54 , 55 , 61 ], and five studies (1619 participants) compared the long-term outcomes between surgery and conservative treatment in patients with recurrent RPS [ 29 , 30 , 37 , 39 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flow diagram showing the entire review process from the original search to the final selection of studies is presented in Fig 1 . In total, 17 studies (3875 participants) compared between extended resection and tumour resection alone [ 10 , 19 , 20 , 22 , 23 , 31 , 32 , 38 , 44 , 45 , 48 , 51 , 53 , 56 , 57 , 59 , 60 ]. Meanwhile, 26 studies (17368 patients) reported data on different surgical resection margins [ 12 , 17 , 18 , 20 , 21 , 24 28 , 33 – 36 , 40 43 , 46 , 47 , 49 , 50 , 52 , 54 , 55 , 61 ], and five studies (1619 participants) compared the long-term outcomes between surgery and conservative treatment in patients with recurrent RPS [ 29 , 30 , 37 , 39 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were seven studies [ 20 , 31 , 32 , 38 , 45 , 48 , 53 ] (790 patients) that reported disease-free survival, and they were pooled in a random-effects model. The results showed no significant difference between the extended resection group and the tumour resection alone group (HR: 1.00; 95% CI: 0.74–1.27; P = 0.945; S1 File ), with low heterogeneity ( I 2 = 23%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Relapse-free survival (RFS) was de ned as the time from surgery to the time of relapse diagnosis [13] .…”
Section: De Nitionmentioning
confidence: 99%
“…Surgical resection is the mainstay of therapy for RPLS and is the only curative treatment available (2,3,7), and the roles of radiotherapy and chemotherapy in the management of RPLS remain controversial (8)(9)(10)(11)(12)(13). Although RPLS metastasis is uncommon, local tumor recurrence occurs in >50% of patients after surgery (14,15). Moreover, 70% of RPLSrelated deaths are due to local recurrence rather than distant metastasis or other reasons (8,16).…”
Section: Introductionmentioning
confidence: 99%